Pembrolizumab for treatment-related neuroendocrine prostate carcinoma with a high tumor mutational burden: a case report - Shiba, Keiji; Fujiwara, Motohiro; Onuki, Ayaka; Kato, Daisuke; Shirakawa, Takeshi; Shimizu, Yohei; Amemiya, Takumasa; Nenohi, Tsunehiro; Matsumoto, Yuki; Urushibara, Masayasu; Kano, Hideto; Ishizaka, Kazuhiro; et al. (Frontiers in Oncology, 2025)
Pembrolizumab has emerged as a significant therapeutic option for the treatment of solid tumors with a high tumor mutational burden (TMB-high). However, there have been no reports of its use in treatment-related neuroendocrine prostate carcinoma (t-NEPC) with TMB-high. We present the case of a 66-year-old man with metastatic prostate cancer (adenocarcinoma with a Gleason score of 4 + 5, initial prostate-specific antigen [PSA] level of 267 ng/mL, clinical stage T3bN0M1b) who was initially treated with doublet therapy, including apalutamide and leuprorelin, leading to a reduction in circulating levels of PSA < 0.001 ng/mL. However, 35 months after diagnosis, a retroperitoneal mass developed and neuron-specific enolase (NSE) levels were elevated 62.6 ng/mL. Computed tomography-guided biopsy of the tumor confirmed metastasis of t-NEPC, while genetic profiling revealed a TMB-high status. Pembrolizumab treatment was initiated at the 39-month after diagnosis. At the 41-month after diagnosis, a 75% reduction in the retroperitoneal mass and a decrease in NSE levels to 31 ng/mL were observed. This case suggests that pembrolizumab is a potential treatment option for t-NEPCs with TMB-high.